GPA as a predictor of helpful behavior: an accounting student sample. Issue 3 (13th March 2017) - Lyons, Paul; Bandura, Randall P.
Abstract : Purpose: The purpose of this paper is to demonstrate the value of student grade point average (GPA) as a predictor of pro-social, helpful behavior. This voluntary behavior has been shown to be highly valuable to managers and co-workers. GPA is not only predictive of success in core tasks on the job, it is also predictive of voluntary, helpful behavior. Design/methodology/approach: The review of literature on predictive value of GPA, in general, as well as that of contextual and helpful behavior on the job is followed by the report of a study with accounting students. The study helps to explain the predictive value of GPA and identifies measures useful in identifying helpful behavior. Findings: Findings indicate that two, brief, reliable surveys (contextual performance, job dedication), grounded in several research studies are highly related to voluntary, helpful behavior on the job. The relationships are based on observations of the supervisors of the employees. Regression analysis also provides relatively strong prediction equations. Practical implications: Studies of GPA have focused almost exclusively on the relationship of GPA with job longevity, financial compensation, and technical skill performance. This paper helps demonstrate the positive relationship of the GPA metric with contextual, pro-social, helpful employee behavior. Originality/value: In the past 35 years research has illuminated the concept that voluntary, helpful employee behavior is as important or even more important than technical skill performance when it comes to unit and/or organizational performance. Very little research has been completed to date to demonstrate that GPA, as a predictor variable, does more than predict skill performance and success on the job. The present study helps to extend the value of GPA as a predictor of success.